Ωk algorithm for multi‐receiver synthetic aperture sonar based on exact analytical two‐dimensional spectrum. Issue 20 (24th September 2019) - Wang, Jinbo; Tang, Jinsong; Tian, Zhen
Abstract : Based on the method of deriving two‐dimensional wavenumber spectrum by using instantaneous Doppler wavenumber in bistatic synthetic aperture radar, the analytical solution of two‐dimensional wavenumber spectrum of multi‐receiver synthetic aperture sonar (SAS) was deduced, and the analytical expression of the half‐quasi‐bistatic angle was obtained under the non‐stop‐and‐go assumption. Based on the derived two‐dimensional wavenumber spectrum, the ωk algorithm suitable for multi‐sub‐array SAS was proposed, which solved the problem that using the displacement phase centre approximation cannot well adapt to the wide mapping area imaging, and the correctness and validity of the algorithm have been verified by the simulation data and the lake experiment data.